Plasma for Bio-Decontamination, Medicine and Food Security - Machala, Zdenko; Hensel, Karol; Akishev, Yuri.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2012)
Non-thermal (cold) plasmas at atmospheric pressure have recently found many breakthrough applications in biology, medicine, and food security. Plasmas can efficiently kill bacteria, yeasts, moulds, spores, biofilms and other hazardous microorganisms, including potential bio-terrorism agents. They can be employed for bio-decontamination and sterilization of surfaces, medical instruments, water, air, food, even of living tissues without causing their damage. Direct or indirect plasma interaction with living cells of microorganisms or even humans enables novel bio-medical applications, e.g. treatment of skin diseases and ulcers. Plasma-enhanced blood coagulation coupled with its antiseptic properties proved success in wound healing and opens new possibilities in surgery, emergency medicine and military applications. Plasma treatment allows cell manipulations, their removal and targeted transfer into the injured area, which can accelerate wound healing. Plasma induced apoptosis (programmed cell death) of tumor cells brings forth a great potential for cancer treatment. Besides, plasma enables painless treatment of dental caries, root canal disinfection, and other dentistry applications. This book is a selection of reviewed manuscripts issuing from the NATO Advanced Research Workshop Plasma for bio-decontamination, medicine and food security held in Jasná, Slovakia, on 15-18 March 2011. It provides a comprehensive overview of the current knowledge and research activities focused at the plasma applications in areas such as bio-decontamination, water chemistry, effects on cells; biofilm inactivation, UV sterilization, and medicine, especially tissue treatment and wound healing, as well as dentistry and food security.
Keywords: Physics; Food science; Dentistry; Medicine; Microbiology; Physics; Plasma Physics; Microbiology; Medicine/Public Health, general; Dentistry; Food Science